Compound Words: Implementation in English Language Teaching - Muhammad Gilar Yudha Pratama (IJECA (International Journal of Education and Curriculum Application), 2018)
Teaching English in Indonesia is implemented through the teaching of EFL (English as a foreign language). Teaching and learning English as a second language poses a challenge for both teachers and students. Problems that arise such as lack of student motivation, changing curriculum, monotonous learning, lack of teacher creativity, and lack of linguistic knowledge in teaching become a separate issue. This article describes the role linguistic morphology plays in teaching and learning English in the classroom. It particularly describes the challenge of combining simple compound words with morphological forms created by the teacher. This teaching design will be applied to 7th grade junior high school students. This simple design will introduce how to combine noun and adjective using the daily context familiar to the students. The researcher expects to see the challenges the teachers will face during the application of the design in the classroom and how they create ways to deal with the challenges.